PENGETAHUAN DAN SIKAP IBU TERHADAP INISIASI MENYUSUI DINI (IMD) DI PMB LISMARINI PALEMBANG - Junay Darmawati; Maritje Rombe; Zulaikha Agustinawati; Afwan Syarif (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2023)
Background: Early Initiation of Breastfeeding is the process of breastfeeding babies immediately after birth, where babies are allowed to find their own mother's nipple (not thrust into the nipple). The purpose of this study was to obtain an overview of the knowledge, attitudes of mothers and the role of midwives towards early breastfeeding initiation (IMD) at BPM Lismarini Palembang. Method: This study used a descriptive survey method with a